Alternative communication tools for the elderly in times of restricted social contacts - Tušer, Irena; Pupíková, Jana; Polcarová, Eliška; Urban, Rudolf; Zeman, Tomáš; Havránková, Renata; Čírtková, Ludmila; Brečka, Tibor A; Kličková, Hana; Navrátil, Leoš (Vojenské zdravotnické listy, 2024)
Background and objective: Nursing homes are threatened by external and internal threats, effect of which may result in a crisis situation (state of emergency). While managing an already existing emergency, it is necessary to create conditions allowing the elderly to maintain their fundamental human and civil rights. Any interference with human and civil rights is acceptable only in a state of emergency when crisis measures are applied. Social isolation was one of the emergency measures within the Covid-19 pandemics and involuntary social isolation may result in one ́s state of depression. To eliminate this prediction, it is necessary to create such conditions that enable the elderly to maintain their basic human needs as well as civil rights. The authors therefore aim to identify and evaluate the effectiveness of possible alternative communication tools and strategies in the nursing homes along with the ways of a potential reduction of negative effects of social contacts restrictions.Methods: On the basis of an online questionnaire, a community of experts evaluated alternative communication tools on a scale from 1 to 5, considering three factors: 1. benefit for the elderly; 2. financial requirements for purchasing/provision for a nursing home; 3. organization requirements for a nursing home. A cost-benefit evaluation was performed to determine a ranking of individual alternative tools.Results: The acquired results of questionnaire survey served as a tool to determine the ranking of importance of individual alternative communication tools that are feasible depending on specific conditions of a nursing home.Conclusion: The research identified useful tools that may help in the nursing homes to mitigate the impacts resulting from restrictions applied in the state of emergency and associated initiatives in the field of mental health.
Keywords: průzkumy a dotazníky; Surveys and Questionnaires; duševní zdraví; komunikace; Aged; Social Isolation; COVID-19; Nursing Homes; Humans; Communication; sociální izolace; senioři; lidé; pečovatelské domovy; Mental Health